Postharvest starch and sugars adjustment in potato tubers of wide-ranging dormancy genotypes subjected to various sprout forcing techniques - Muhammad Wasim Haider; Muhammad Nafees; Rashid Iqbal; Habat Ullah Asad; Farrukh Azeem; Baber Ali; Ghazala Shaheen; Javed Iqbal; Shweta Vyas; Muhammad Arslan; Muhammad Habib Ur Rahman; Mohamed S. Elshikh; et al. (Scientific Reports, 2023)
Abstract The development of an efficient, safe, and environment-friendly technique to terminate tuber dormancy in potatoes (Solanum tuberosum L.) is of great concern due to the immense scope of multiple cropping all over the globe. The breakage of tuber dormancy has been associated with numerous physiological changes, including a decline in the level of starch and an increase in the levels of sugars during storage of freshly harvested seed potatoes, although their consistency across genotypes and various dormancy-breaking techniques have not yet been fully elucidated. The purpose of the present research is to assess the efficacy of four different dormancy-breaking techniques, such as soaking in 90, 60, or 30 mg L−1 solutions of benzyl amino purine (BAP) and 30, 20, or 10 mg L−1 gibberellic acid (GA3) alone and in the combination of optimized concentrations; cold pre-treatment at 6, 4, or 2 °C; electric shock at 80, 60, 40, or 20 Vs; and irradiation at 3.5, 3, 2.5, 2, 1.5, or 1 kGy on the tuber dormancy period and sprout length of six genotypes. Furthermore, the changes that occurred in tuber weight and endogenous starch, sucrose, fructose, and glucose contents in experimental genotypes following the application of these techniques were also examined. Overall, the most effective technique to terminate tuber dormancy and hasten spout growth was the combined application of BAP and GA3, which reduced the length of dormancy by 9.6 days compared to the untreated control, following 6.7 days of electric current, 4.4 days of cold pre-treatment, and finally irradiation (3.3 days). The 60 mg L−1 solution of BAP greatly reduced the dormancy period in all genotypes but did not affect the sprout length at all. The genotypes showed a weak negative correlation (r =  − 0.4) (P < 0.05) of endogenous starch contents with dormancy breakage and weight loss or a moderate (r =  − 0.5) correlation with sprout length, but a strong positive correlation (r = 0.8) of tuber glucose, fructose, and sucrose contents with dormancy breakage and weight loss. During 3 weeks of storage, sprouting commencement and significant weight loss occurred as tuber dormancy advanced towards breakage due to a reduction in starch and an increase in the sucrose, fructose, and glucose contents of the tubers. These findings could be advantageous for postponing or accelerating seed potato storage as well as investigating related physiological research in the future.